Soil Impacts on the Natural Vegetation of the Tropical and Sub Alpine Region of Central Himalayas - Bhandari, Samir; Hamal, Jaya Prakash; Bhandari, Amir (Amrit Journal, 2025)
In the Central Himalayas' tropical and sub-alpine regions, a study was conducted to analyze the impact of soil on natural vegetation. The study took place in the Dolakha and Sindhupalchowk districts and involved ecological sampling in six different forest types at various elevations. The random sampling method with circular plots of different radius viz. 10m, 2.5m & 1m to sample trees, shrubs, and herbs were utilized respectively. The study examined various soil properties, including texture, pH, water holding capacity, sticky point, water rising and percolation. The analysis revealed that the Mixed Broadleaf Forest soil had the highest water holding capacity (86.97%), while the Sal Forest in Sukute had the lowest. In terms of soil pH, the Rhododendron-dominated Forest had the least acidic soil with a pH of 6.45, whereas the Pine Forest and Taxus wallichiana-dominated forest had more acidic soil with a pH of 5.6. The study also found that the sticky point of the Mixed Broadleaf Forest soil was 47.46%, indicating it was much drier, while the Sal Forest in Sukute soil was very wet with a sticky point of 22.73%. The results of this study suggest that vegetation patterns are influenced by a combination of topographic, edaphic factors and change in climatic conditions.